PROBLEMS OF FORMATION AND DEVELOPMENT OF HIGHER AUTHORITIES IN GEORGIA (1991 - 2018) - A. Bagaeva (Гуманитарные и юридические исследования)
The process of state-building in post-Soviet republics was accompanied by a demonstration of their commitment to different political systems, different socio-economic models. These republics had their own assessments of the common history and vision of national interests, which did not coincide with the interests of other post-Soviet republics. Especially in this respect, Georgia stood out: after the events of August 2008. State-building in this republic was influenced by a number of negative factors that complicate the political situation in this country and in the South Caucasus region as a whole. These events aroused interest in them on the part of Russian researchers: their study was updated in connection with the growing threats to Russia's national security along the entire perimeter of its Caucasian borders. The novelty of the research is the study of the specific form of power in Georgia, which depends on the national- historical features and Georgian cultural traditions. The study found that political institutions were created in Georgia with some regard for other post-Soviet countries, but in general it followed its own path of development. The author's attention is focused on the problems that negatively affect the process of state-building in Georgia - radical nationalism, civil confrontation, ethno-political problems, etc. As a result of their detailed analysis, the author of the article concluded that the constitutional reform as a whole contributed to the replacement of the presidential form of government with a parliamentary one, but the lack of a legal framework for the functioning of democratic institutions negated the efforts of the Georgian leadership to create a socially oriented, democratic state.